The Contribution of the Tandem App on Tourism Undergraduates’ Speaking Fluency in English - Agurto, Miguel; Cisterna, Cecilia; Parra, Jeanette (Colombian Applied Linguistics Journal, 2024)
Speaking English fluently in social and professional settings has become a major requirement in the Tourism industry. With this in mind, this action research study explores how the Tandem application supports the speaking fluency of Tourism students in English. The study’s sample was comprised of seven participants from a Chilean professional institute who took part in four weekly online intervention sessions. Participants used the Tandem app to communicate with native and non-native speakers of English through voice messages during and after the intervention sessions. Their oral fluency was assessed by contrasting their speech rate and use of long pauses during a pre-and a post-session English fluency interview. Additionally, participants´ perceptions were collected through a semi-structured interview conducted in Spanish. Findings revealed that there was a slight, but nonetheless statistically significant in accordance with the Wilcoxon test, improvement in the fluency of their speaking. Participants agreed that the use of the application as a tool was beneficial and helped them to increase their speaking fluency and confidence by interacting with native and non-native speakers of English.